Eucalyptus grandis WRKY genes provide insight into the role of arbuscular mycorrhizal symbiosis in defense against Ralstonia solanacearum - Zhang, Jianlang; Yang, Xinzhu; Huo, Chunyu; Fan, Xinyi; Liu, Qiutong; Liu, Zhihong; Su, Yu; Chen, Zujing (Frontiers in Plant Science, 2025)
IntroductionWRKY transcription factors are essential for plant growth, health, and responses to biotic and abiotic stress.MethodsIn this study, we performed a deep in silico characterization of the WRKY gene family in the genome of Eucalyptus grandis. We also analyzed the expression profiles of these genes upon colonization by the arbuscular mycorrhizal fungus (AMF) Rhizophagus irregularis (Ri) and infection with the bacterial pathogen Ralstonia solanacearum (Rs).ResultsA total of 117 EgWRKYs were identified. Phylogenetic analysis divided the EgWRKY proteins into three groups: group I (21 proteins, 17.95%), group II (65 proteins, 55.56%), and group III (24 proteins, 20.51%). Additionally, seven EgWRKY proteins (5.98%) were categorized into group IV due to the absence of the WRKY domain or zinc-finger structure. All EgWRKY genes are distributed irregularly across the 11 chromosomes, with 25 pairs identified as segmental duplicates and four as tandem duplicates. The promoter regions of 50% of members of each subfamily contain plant hormone-related cis-elements associated with defense responses, such as ABREs, TGACG motifs, and CGTCA motifs. All subfamilies (except for group IV-b and IV-c) contain AW-boxes, which are related to mycorrhizal induction. Furthermore, transcriptomic analysis revealed that 21 EgWRKYs were responsive to the AMF Ri, with 13 and 8 genes strongly up- and downregulated, respectively. Several genes (including EgWRKY116, EgWRKY62, and EgWRKY107) were significantly induced by Ri; these genes might enhance the defense of E. grandis against Rs.DiscussionTherefore, we identified E. grandis WRKY genes that are regulated by AMF colonization, some of which might improve the defense of E. grandis against R. solanacearum. These findings provide insights into E. grandis WRKY genes involved in interactions among the host plant, AMFs, and R. solanacearum.